2014
DOI: 10.1016/j.leukres.2013.12.014
|View full text |Cite
|
Sign up to set email alerts
|

The AML1/ETO target gene LAT2 interferes with differentiation of normal hematopoietic precursor cells

Abstract: The adaptor protein linker activator of T-cells 2 (LAT2) is a known AML1/ETO target gene whose function during normal hematopoiesis is unknown. We addressed the role of LAT2 during erythroid and myeloid differentiation of normal human CD34+ hematopoietic cells. LAT2 is expressed at low levels in CD34+ cells and upregulated during cytokine-induced myeloid and erythroid differentiation. Forced LAT2 expression leads to a delay of erythroid and myeloid differentiation keeping CD34+ cells in a more immature state, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…NTAL protein levels are significantly decreased in a time-dependent manner in NB4 cells (an acute promyelocytic leukemia [APL] cell line) treated with all-trans retinoic acid (ATRA). Similarly, decreased NTAL expression has also been observed in other AML cell lines treated with drugs that induce differentiation 9,10 . In APL, NTAL depletion from lipid rafts in response to arsenic trioxide (ATO) decreases cell viability through regulation of the Akt/PI3K pathway 11 .…”
mentioning
confidence: 69%
See 1 more Smart Citation
“…NTAL protein levels are significantly decreased in a time-dependent manner in NB4 cells (an acute promyelocytic leukemia [APL] cell line) treated with all-trans retinoic acid (ATRA). Similarly, decreased NTAL expression has also been observed in other AML cell lines treated with drugs that induce differentiation 9,10 . In APL, NTAL depletion from lipid rafts in response to arsenic trioxide (ATO) decreases cell viability through regulation of the Akt/PI3K pathway 11 .…”
mentioning
confidence: 69%
“…NTAL is reported to be expressed in acute myeloid leukemia (AML) cells, but its expression varies significantly among the different subtypes of AML 9 . NTAL expression in primary AML blasts has already been found to be associated with myelomonocytic features 10 .…”
mentioning
confidence: 99%
“…The significant expression and the general clues provided by the protein sequence and structure suggested that Runx1t1 might act as a regulator to modulate development of the nervous system. Several studies have suggested that Runx1t1 was involved in the proliferation and affected the differentiation capacity of the hematopoietic progenitors [18,[27][28][29]. Despite extensive efforts to understand the function of Runx1t1 protein in the etiology of cancer, the lack of knowledge about their function in normal embryonic development continues to persist.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, if there are selfrenewing stem cells among cancer cells, the sphere culture system might be able to isolate cancer stem cells from a pool of cancer cells. Hence, investigations of the formation process and the chemosensitivity of cancer cell colonies are crucial in cancer research (Liu et al, 2012;Lee et al, 2014;Essig et al, 2014). The colony formation assay became a gold standard for measuring the development of early tumors and the effects of cytotoxic agents on tumors in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…However, conventional bio-assays quantifying indicative cellular components are ineffective especially for large cancer cell colonies. Currently, quantification of cancer cell colonies is achieved by manual counting under microscope (Liu et al, 2012;Lee et al, 2014;Essig et al, 2014;Jin et al, 2013). Because cell colonies are suspended in 3D hydrogel and present irregular shapes, this is challenging to microscopically quantify the colony number and size without subjective bias.…”
Section: Introductionmentioning
confidence: 99%